Triumph in Adversities: Psychological Trauma and Resilience through the Lens of Families of Ambush Victims - Atienza, Maria Elaine (Journal of Interdisciplinary Perspectives, 2025)
This study explored the experiences of children whose parents were victims of ambushes in Luzon, Philippines, using a qualitative phenomenological approach. Five participants from Cavite, Laguna, Palawan, Manila, and Makati shared their stories. The data were analyzed through Interpretative Phenomenological Analysis (IPA), revealing several key themes about their emotional, psychological, and social challenges. These themes highlighted how the children coped with emotional turmoil, adjusted their routines, and found resilience through family and community support. The findings emphasized the critical role of support systems in helping children heal and adapt after traumatic events. This study provides insights into the impact of such tragedies on young individuals. It underscores the need for family and community resilience programs, promoting recovery and long-term well-being.